PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PENGENALAN SATWA LANGKA YANG DILINDUNGI DI INDONESIA BERBASIS AUGMENTED REALITY - Rifda Choirunnisa; Apri Utami Parta Santi (STKIP Subang, 2026)
This research is motivated by the need for digital learning media that is attractive, easy to use, and able to facilitate students' understanding of the material in learning Natural and Social Sciences (IPAS). The purpose of the research is to develop interactive learning media based on Augmented Reality on the material